1928
DOI: 10.1021/ja01395a026
|View full text |Cite
|
Sign up to set email alerts
|

STUDIES ON THE REACTIONS RELATING TO CARBOHYDRATES AND POLYSACCHARIDES. XVI. SEPARATION AND IDENTIFICATION OF THE ISOMERIC ETHYLIDENE GLYCEROLS1

Abstract: An experiment carried out with 3 g. of 1,2-benzylidene glycerol, similarly treated with dry hydrogen chloride but without any preliminary heating and allowed to stand for one month at room temperature, yielded 0.45 g. of 1,3-benzylidene glycerol.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

1930
1930
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(4 citation statements)
references
References 0 publications
1
3
0
Order By: Relevance
“…After removal of the volatiles under reduced pressure, this two‐step procedure afforded acetal in high yield and good GC‐MS purity (96.5% and 94.3%, respectively), thereby allowing the use of the crude product without further purification. As expected, 33 13 C NMR analysis of the sample revealed the presence of six distinct acetal compounds, whose C2 carbon atoms were found to resonate in the δ C = 101–105 ppm region. Based on previous spectroscopic studies on glycerol acetals of long‐chain aldehydes, 34 , 35 the NMR constants recorded for the sample were consistent with a mixture of trans and cis 1,3‐dioxolane and 1,3‐dioxane derivatives (Fig.…”
Section: Resultssupporting
confidence: 79%
“…After removal of the volatiles under reduced pressure, this two‐step procedure afforded acetal in high yield and good GC‐MS purity (96.5% and 94.3%, respectively), thereby allowing the use of the crude product without further purification. As expected, 33 13 C NMR analysis of the sample revealed the presence of six distinct acetal compounds, whose C2 carbon atoms were found to resonate in the δ C = 101–105 ppm region. Based on previous spectroscopic studies on glycerol acetals of long‐chain aldehydes, 34 , 35 the NMR constants recorded for the sample were consistent with a mixture of trans and cis 1,3‐dioxolane and 1,3‐dioxane derivatives (Fig.…”
Section: Resultssupporting
confidence: 79%
“…GEA consists of an isomeric mixture of five- and six-membered ring acetals in both cis and trans forms including the following compounds: cis -5-hydroxy-2-methyl-1,3-dioxane, trans -5-hydroxy-2-methyl-1,3-dioxane, cis -4-hydroxymethyl-2-methyl-1,3-dioxolane, and trans -4-hydroxymethyl-2-methyl-1,3-dioxolane . There are two main routes for the synthesis of this product: direct acetalization of glycerol with acetaldehyde (eq ) and transacetalization by reacting glycerol with 1,1-diethoxyethane (DEE). ,− The acetalization route was used in this work, because its only disadvantage is the formation of water, which is undesirable in the final fuel additive. However, water-free GEA solution can be obtained by the use of an integrated reaction–separation technology, such as the simulated moving-bed reactor, which has already proved to be efficient in other acetalization processes. Moreover, this route avoids the more complex reaction scheme of the transacetalization process with several reaction and separation units (usually, one reactor for the production of DEE from acetaldehyde and ethanol, a distillation column for separating DEE, a reactor for the synthesis of GEA from DEE and glycerol, and a distillation column for separating the final product).…”
Section: Introductionmentioning
confidence: 99%
“…Few studies about the synthesis of GEA have been published to date, and most of them present some inconsistencies , or make use of solvents and/or homogeneous catalysts. , However, a heterogeneous catalyzed continuous process for the synthesis of GEA was reported by Miller et al In this process, GEA is produced by reacting the outlet stream of a transesterification reactor, containing an FAE and glycerol, with acetaldehyde. A mixture comprising the fuel and the GEA additive is obtained as the outlet stream without the need to introduce the additive in the fuel composition at another stage of the process.…”
Section: Introductionmentioning
confidence: 99%
“…Compound 113 would be expected to exist as a mixture of diastereomers, and since the crystalline product was isolated in good yield, which suggests that a second isomer was not present or was present only in small amount, it indicates that the reaction had not reached equilibrium and that 113 was the product of kinetic control. Similarly benzylidenation of 1,6-dl-O-benzoylgalactitol has yielded121-123 two of the three possible stereoisomers of 1,6-di-0-benzoyl-2,3:4,5-di-0-benzylldene-(DL)-galactltol (115,116, and 117) rather than the 2,4:3,5-dlacetal 118 with two axial -CH2OBz groups. An examination103 of these products by 1H NMR spectroscopy showed that the lower melting isomer had two discrete benzylic proton signals and Is clearly the dl form 115, whereas the second isomer with the higher melting point showed only a single signal and is therefore one of the meso forms 116 or 117.…”
Section: Stereochemistry Of Monocyclic Acetalsmentioning
confidence: 99%